PERANCANGAN DESAIN BASIS DATA SISTEM INFORMASI GEOGRAFIS TANAH PENDUDUK DENGAN MENERAPKAN MODEL DATA RELASIONAL ( STUDI KASUS : DESA TUMBANG MANTUHE KABUPATEN GUNUNG MAS PROVINSI KALIMANTAN TENGAH ) - Constantin Menteng; Afis Julianto; Adi Surya; Ema Utami; Tri Amri Wijaya (Universitas Palangka Raya, 2021)
Database design is a data design process that is used to support the operational activities and goals of organizations and agencies. The use of databases on the geographic information system of residents' lands makes it possible to store, change, and display all data quickly and easily. One of the factors that become a problem in database design is the point of view of seeing data that varies between designers, programmers, and end-users. Therefore we need a methodology in good database design by applying procedures, techniques, tools, and documentation. The method used in this study used the Research and Development (R&D) method, while the database design method used the Database Life Cycle (DBLC) method. The research variables were database design for the geographic information system of resident land with a relational data model. Research aspects include conceptual design, logical design, and physical design. The final result of this research is to produce 10 types of conceptual entities, produce a relationship diagram of the ten logical entities, and produce a physical design consisting of user_admin, user_pengguna, data_desa, data_kecamatan, data_kabupaten, jenis_tanah, data_penduduk, data_buku_c, data_mutasi, and data_sppt tables.